Association of serum lycopene with low-frequency hearing loss in adults in their 70s based on NHANES database - Yuan Wang; Huifen Yang; Caiqin Huang (Scientific Reports)
Abstract Age-related hearing loss is the third most common health condition affecting elderly individuals. The relationship between lycopene in blood and sensorineural hearing loss in elderly adults has rarely been reported. This study aimed to elucidate the connection between serum lycopene levels and sensorineural hearing loss among elderly individuals. This cross-sectional study included 693 participants aged 70–80 years from the National Health and Nutrition Examination Survey (NHANES) from 2017 to 2018. The outcomes included sensorineural low-frequency hearing loss [pure-tone average (PTA) at 0.5, 1, and 2 kHz ≥ 20 dB], speech-frequency hearing loss (PTA at 0.5, 1, 2, and 4 kHz ≥ 20 dB), and high-frequency hearing loss (PTA at 4, 6, and 8 kHz ≥ 20 dB). Multivariate logistic regression analysis was used to determine the relationship between lycopene in blood and the risk of hearing loss. There were 418 (60.3%), 522 (75.3%), and 667 (96.2%) participants who experienced hearing loss at low, speech, and high frequencies, respectively. Serum total lycopene (OR = 0.575, 95% CI 0.337–0.984) and serum cis-lycopene (OR = 0.334, 95% CI 0.112–0.994) were associated with a lower risk of low-frequency hearing loss after adjusting for covariates. Among male participants, the serum total, cis-, and trans-lycopene levels were inversely related to low- and speech-frequency hearing loss. However, no relationship was observed among the female participants. In conclusion, our findings indicate that increased serum lycopene levels are associated with a decreased prevalence of sensorineural low-frequency hearing loss in older adults, especially in men.